Pengaruh Kompensasi dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT. Markasia Communication - Miftahul Rifa Sabtina; Rani Kurniasari (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This study aims to determine how the influence of influence and work discipline on the performance of employees at PT. Markasia Communications. PT. Markasia Communication is a full services marketing communication founded in 2008 with a company that has a proven track record of delivering the best results to its clients. PT services Markasia Communication consists of events, designs, and multimedia presented in a creative, unique and integrated approach to meet client needs. This research focuses on employees. PT. Markasia Communication located in South Jakarta. A company in achieving good performance and employee discipline to always be orderly, one of which can be influenced by compensation. This research method uses a quantitative. The sampling technique used was saturated sampling technique. Data collection techniques in this study used observation and questionnaire techniques. The data obtained from the questionnaire with the number of respondents as many as 35 employees. The research obtained is based on the simultaneous test (F) that the variables of pressure and work discipline simultaneously have a significant effect on employee performance, where the calculated F value is greater than F table (45.050 > 3.290 , with a significance value smaller than the significance level (0.00 Based on the t test for the coercion and work discipline variables, it has a significant positive effect on the acquisition of a positive beta value of 0.375 and a significance value of 0.006 which is less than 0.05 (0.005 < 0.05), and the t test results for the work discipline variable obtain a positive beta value of 0.553 and a significance value of 0.000 is less than 0.05 (0.000 <0.05).